Towards More Effective Feedback Strategies to Enhance Microteaching for Pre-service Teachers at ISEAH Mahdia - Najla Fki (Studies in Applied Linguistics & TESOL, 2023)
This exploratory practice study examined the effectiveness of the feedback strategies currently in use at the Higher Institute of Applied Studies in the Humanities of Mahdia in relation to the practice of microteaching for Tunisian pre-service teachers. Qualitative and quantitative data from third-year students majoring in Education and Teaching were collected: 30 videotaped microteaching lessons, two in-class discussions, and teacher trainees’ responses to a survey designed to track their progress in light of the feedback they had received from their trainer and peers. The analyses revealed traceable improvement in the trainees’ understanding and performance, thereby establishing the efficacy of the current feedback strategies for enhancing the quality of students’ microteaching.